2017
DOI: 10.1111/eip.12412
|View full text |Cite
|
Sign up to set email alerts
|

Age at onset and the outcomes of schizophrenia: A systematic review and meta‐analysis

Abstract: The aim of this study was to analyse the effect of age at onset on the long‐term clinical, social and global outcomes of schizophrenia through a systematic review and a meta‐analysis. Original studies were searched from Web of Science, PsycINFO, Pubmed and Scopus, as well as manually. Naturalistic studies with at least a 2‐year follow‐up were included. Of the 3509 search results, 81 articles fulfilled the inclusion criteria. The meta‐analysis was performed in Stata as a random‐effect analysis with correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
128
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(148 citation statements)
references
References 63 publications
14
128
4
2
Order By: Relevance
“…Our results showed that age, age at onset, initial symptom severity, and MMN amplitude at the Fz site could predict schizophrenia remission. The result was consistent with previous studies in which age at onset and baseline PANSS scores predicted remission [32,33]. Besides the clinical variables, biological markers, such as MMN, might predict schizophrenia remission.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that age, age at onset, initial symptom severity, and MMN amplitude at the Fz site could predict schizophrenia remission. The result was consistent with previous studies in which age at onset and baseline PANSS scores predicted remission [32,33]. Besides the clinical variables, biological markers, such as MMN, might predict schizophrenia remission.…”
Section: Discussionsupporting
confidence: 92%
“…A further interesting avenue of investigation for negative symptom development is the role of protective factors, which may impact on negative symptom reserve. Individuals with short DUP (Boonstra et al, 2012), older age of onset (Immonen, Jaaskelainen, Korpela, & Miettunen, 2017), more years in education (Clarke et al, 2006), female sex (Leung & Chue, 2000) and married marital status (Makinen et al, 2010) have been shown to have better negative symptom outcomes. Several of these factors are stable regardless of interventions delivered, and an evaluation of whether risk or protective factors for negative symptoms are malleable is an important consideration (Harrigan, McGorry, & Krstev, 2003).…”
Section: Negative Symptom Reserve Theorymentioning
confidence: 99%
“…Clinical symptoms are often classified in three main domains: positive symptoms, such as hallucinations, delusions, suspiciousness/persecution; negative symptoms, such as emotional withdrawal, blunted affect, and passive social withdrawal; and cognitive symptoms, such as impaired perception, learning, thinking, and memorizing. EOS may be accompanied by greater symptom severity, premorbid developmental impairment, 'soft' neurological signs (eg, clumsiness, motor incoordination), and a higher rate of substance abuse (Hsiao and McClellan, 2008;Clemmensen et al, 2012;Immonen et al, 2017). Accordingly, diagnosis of EOS is often difficult and frequently delayed since onset is more commonly insidious than acute, which makes it difficult to differentiate EOS from underlying cognitive deficits, premorbid functional impairment, or other abnormalities (Russell, 1994;Bartlet, 2014).…”
mentioning
confidence: 99%
“…Although early intervention is associated with improvement in negative symptoms (Boonstra et al, 2012), this may be challenging since negative symptoms develop slowly and may be difficult to detect or differentiate from other clinical features (Kirkpatrick et al, 2001;Galderisi et al, 2018). Moreover, a more insidious onset predicts poorer outcome and more severe negative symptoms (Kao and Liu, 2010;Immonen et al, 2017;Murru and Carpiniello, 2018). Diagnosis of patients with predominantly negative symptoms (lacking manifest psychotic signs) is often delayed, resulting in a longer duration of untreated psychosis.…”
mentioning
confidence: 99%